Factors for Oral Intake Recovery in Acute Illness Patients With Dysphagia: A Prospective Cohort Study - Sho Nishiguchi; Nagisa Sugaya; Miyo Akiyama; Masahiko Inamori (Health Science Reports, 2025)
ABSTRACT Background and Aims This study examined to identify predictive factors for oral intake recovery in patients with acute illness after discharge from an acute care hospital. Methods The prospective cohort study was conducted at an acute care hospital between January and December 2020. Among 3359 consecutive patients who required speech therapy rehabilitation after acute illness treatment, those with oral intake difficulty were selected. After discharge, patients were followed up at home care service, long‐term care facility, or sub‐acute hospital. Difficulty in oral intake was defined based on the dysphagia grade by speech‐language pathologists and overall oral intake consumption. The primary outcome measure was the recovery of total oral intake 90 days after discharge. We analyzed the clinically relevant factors for oral intake recovery using a multivariate logistic regression model. Results Among 512 patients with severe dysphagia and insufficient oral intake upon discharge, 410 were ultimately included (response rate: 80.0%) from 106 facilities, comprising a home care service, a long‐term care facility, and another hospital. The mean age was 83.2 years, with 52.9% of the patients being men. The median length of the hospital stay was 27 days. Overall, 195 (47.4%) patients survived, and 57 (13.9%) recovered their oral intake 90 days after discharge. In the multivariable analysis, the absence of nocturnal suctioning (adjusted odds ratio = 3.8, 95% confidence interval: 1.9–7.5, p < 0.001), communication ability (p = 0.021), and artificial hydration and nutrition (p = 0.001) were significant factors associated with oral intake recovery within 90 days after discharge. Conclusion The factors identified in this study may contribute to prognosis of patients who can recover their oral intake at discharge from acute care hospitals and to the implementation of appropriate discharge plans and artificial hydration and nutrition.